THE EFFECT OF YOGA PRACTICE ON BLOOD PRESSURE IN WOMEN AGED 50 – 59 YEARS IN POSYANDU LANSIA KALIJATEN SIDOARJO - Sari, Dhika Puspita; Kumaat, Noortje Anita (Jurnal Kesehatan Olahraga, 2019)
Aging is a condition that occurs in human life, with increasing age a person's blood pressure will increase. The purpose of this study is to analyze the effect of Yoga exercises on blood pressure in women aged 50 - 59 years in Posyandu Lansia Kalijaten Sidoarjo. The design used in this study is the Pretest-Posttest Control Group. The sample in this study are 20 respondents according to the criteria set by the researcher, using purposive sampling technique. The measuring instrument used in this study is Sphygmomanometer.The statistical test uses the Independent Samples t Test with a significance value of p <0.05. The homogeneity test results showed that the systolic and diastolic variances in the control and experimental groups had the same variance with a significant level p <0.05. The results of two different test averages showed that there were significant differences in systolic and diastolic blood pressure between the control group and the experimental group. This can be seen from the p-value of the Independent Samples t Test <0.05. Based on the data, it can be concluded that there is a significant effect of decreasing systolic and diastolic blood pressure, from category moderate hypertension to normal?high in women aged 50 ? 59 years in Posyandu Lansia Kalijaten Sidoarjo after practicing Yoga. Keyword: Yoga, Blood pressure.